An approach to integrating the remotely sensed, geological, and geophysical data using the Dempster–Shafer mathematical theory - Popov, M.A.; Stankevich, S.A.; Topolnitsky, M.V.; Sedlerova, O.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
A new approach to the integration of remote and geological and geophysical data is proposed and substantiated on the basis the Dempster–Shafer mathematical theory of evidence, which allows one to integrate these data and to build maps of the spatial distribution function of similarity trust with positive structures (established deposits of hydrocarbons). This is the basis for the informational support of a decision-making on the perspective to find oil-gas deposits. The examples of its implementation on areas the Prykerchensky shelf of the Black Sea and in the Azov Sea are given. This approach allows one to quantitatively evaluate the degree of their perspectives and to pose specific problems for further exploration works.